Calibration of centre-of-mass energies at LEP1 for precise measurements of Z properties - Assmann, R; Boge, M; Billen, R; Blondel, A; Bravin, E; Bright-Thomas, P; Camporesi, T; Dehning, B; Drees, A; Duckeck, G; Gascon, J; Geitz, M; et al. (1999)
The determination of the centre-of-mass energies from the LEP1 data for 1993, 1994 and 1995 is presented Accurate knowledge of these energies is crucial in the measurement of the Z resonance parameters The improved understanding of the LEP energy behaviour accumulated during the 1995 energy scan is detailed while the 1993 and 1994 measurements are revised. For 1993 these supersede the previously published values. Additional instrumentation has allowed the detection of an unexpectedly large energy rise during physics fills. This new effect is accommodated in the modelling of the beam-energy in 1995 and propagated to the 1993 and 1994 energies. New results are reported on the magnet temperature behaviour which constitutes one of the major corrections to the average LEP energy. The 1995 energy scan took place in conditions very different from the previous years. In particular the interaction-point specific corrections to the centre-of-mass energy in 1995 are more complicated than previously, these arise from the modified radiofrequency-system configuration and from opposite-sign vertical dispersion induced by the bunch-train mode of LEP operation. Finally an improved evaluation of the LEP centre-of-mass energy spread is presented. This significantly improves the precision on the Z width.